2009
DOI: 10.1016/j.cellbi.2008.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Dual role of HIF‐1α in delivering a survival or death signal in hypoxia exposed human K562 erythroleukemia cells

Abstract: Hypoxia (reduced oxygen tension) is a critical stimulus which switches on a cell rapid response, determining damage and death in some cells, and adaptation and survival in others. Here we report that K562 erythroleukemia cells exposed to hypoxia, proliferated more slowly and the percentage of dead cells increased after 22 h. In parallel HIF (Hypoxia Inducible Factor)-1alpha and Bax level increased, as well as the PKC (Protein Kinase C) delta/Erk (Extracellular Signal Regulated Kinase) pathways being activated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…In favor of this hypothesis, intermittent hypoxia increases survival of APL mice ( 123 ). Similarly, in CML, HIF-1alpha induction following short (5 h) hypoxia exposure delivered a survival signal to cells, whereas it promoted cell death within a longer period (22 h) ( 127 ). In the ALL model, 24 h-exposure to hypoxia conferred chemoresistance in contrast to longer exposure (48–72 h) ( 128 ).…”
Section: Hypoxia-inducible Factors In Leukemiasmentioning
confidence: 99%
“…In favor of this hypothesis, intermittent hypoxia increases survival of APL mice ( 123 ). Similarly, in CML, HIF-1alpha induction following short (5 h) hypoxia exposure delivered a survival signal to cells, whereas it promoted cell death within a longer period (22 h) ( 127 ). In the ALL model, 24 h-exposure to hypoxia conferred chemoresistance in contrast to longer exposure (48–72 h) ( 128 ).…”
Section: Hypoxia-inducible Factors In Leukemiasmentioning
confidence: 99%
“…PKC is also involved in IFN--induced growth inhibition of CML cells through phosphorylation of Stat1 [374]. On the other hand, PKC may also participate in K562 cell death because of a close relationship between activation of the PKC /ERK pathway and high levels of Bax at hypoxia-induced apoptosis [375].…”
Section: And Amlmentioning
confidence: 99%
“…A study of 2009 reported that human leukemia K562 cells show a down regulation of proliferation and an increase of cell death after 22 hours of hypoxia. While 5 hours of hypoxia were able to increase HIF-1 expression, but did not modify cell cycle progression or affect cell death [29].…”
Section: Tumor Hypoxiamentioning
confidence: 99%